INFORMATION TECHNOLOGY AND REMOTE AUDIT DURING COVID 19 PANDEMIC - Nur Rohmah, Safitri; Novianingsih, Rika; Okfitasari, Antin (LPPM Universitas Duta Bangsa Surakarta, 2022)
This study aims to analyze the role of information technology to remote auditing during the covid 19 pandemic. Covid 19 has changed the work style of auditors in the manual/traditional audit process to remote audit, as a solution in dealing with the impact of the pandemic. This condition demands that the auditor profession in preparing or dealing with remote audits will be closely related to the use of information technology. This research method is literature review. The data is obtained from articles uploaded on Google, Google Scholar and Sciencedirect with the keyword: remote audit and information technology. After collecting, a descriptive analysis was carried out to answer the research objectives. The result is that during the COVID-19 pandemic, remote auditing has become a solution to the impacts of covid 19, such as social distancing. Auditors in carrying out remote audits need information technology facilities in the audit process. Information technology has a vital role in remote auditing from planning, working papers, documentation, communication and supervision. Information technology is an integral part of remote auditing.